Crystal growth and Characterization of an NLO material: L-cysteinium Sodium Nitrate Chloride (LCSNC) - Azeezaa, V; Joseph, A Arul Pragasam; Sunitha, T.G (Photonics Letters of Poland, 2014)
In the present work, L-Cysteinium Sodium Nitrate Chloride (LCSNC) an organic nonlinear optical material has been synthesized by slow evaporation method. Crystalline nature was confirmed by single crystals X-ray diffraction analysis. The UV-Vis transmittance spectrum shows that the crystal has a good optical transmittance in the entire visible region with lower cutoff wavelength 203 nm. The various functional groups and chemical compositions of the grown crystal have been derived from FTIR spectral analysis. Both the dielectric constant and dielectric loss decrease with the increase in frequency. The SHG efficiency was measured by employing powder Kurtz method. Full Text: PDF References D.S. Chemla, J. Zyss, Nonlinear optical properties of organic molecules and crystals (Academic Press 1987). CrossRef P.N. Prasad, D.J. Williams, Introduction to Non Linear Optical Effect in Molecules and Polymers, John Wiley & Sons, New York, 1991. CrossRef M. Loganayaki, P. Murugakoothan, "Growth, structural and dielectric behavior of L-Cysteine hydrochloride monohydrate single crystals", Asian J Chem. 23, 5085-5088 (2011). DirectLink G. Bhagavannarayana, S. Kumar, M. Shakir, S.K. Kushawaha, K.K. Maurya, R. Malhotra, K.R. Rao, "Unidirectional growth of L-cysteine hydrochloride monohydrate: first time observation as nonlinear optical material and its characterization", J Appl Cryst. 43, 710-715 (2010). CrossRef J. Packiam Julius, A. Joseph Arul Pragasam, S. A. Rajasekar, S. Selva Kumar, A. Stephen, and P. Sagayaraj, "Studies on the growth and characterization of L-argininium formate single crystals", J Cryst Growth. 267, 619-623 (2004). CrossRef W. Kemp, Organic Spectroscopy, Palgrave Macmillan, 1991. S. Zulifiqar Ali Ahamed, G.R. Dillip, L. Manoj, P. Raghavaiah, B. Deva Prasad Raju, "Growth and characterization of a new NLO material: L-serine sodium nitrate", Photonics Letters Of Poland, 2 (4), 183-185 (2010). CrossRef S. Boomadevi, H.P.Mittal, R. Dhanasekaran, "Synthesis, Crystal Growth and Characterization of 3-methyl 4-nitropyridine 1-oxide, POM) single crystals", J. Cryst. Growth. 261, 55-62 (2004). CrossRef K.V. Rao and A. Smakula, "Dielectric Properties of Cobalt Oxide, Nickel Oxide and Their Mixed Crystals", J. Appl. Phys. 36(6), 2031-2038 (1965). CrossRef B.D. Halton, K. Landskron, W.J. Hunks, "Materials chemistry for low-k materials", Materials Today, 9, 22-31 (2006). CrossRef S.K. Kurtz and T.T. Perry, "A powder technique for the evaluation of non-linear optical materials", J. Appl. Phys. 39, 3798-3813 (1968). CrossRef